2020
DOI: 10.3389/fnins.2020.00294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Vibro-Tactile P300 Based Brain-Computer Interface on the Coma Recovery Scale-Revised in Patients With Disorders of Consciousness

Abstract: Persons diagnosed with disorders of consciousness (DOC) typically suffer from motor and cognitive disabilities. Recent research has shown that non-invasive brain-computer interface (BCI) technology could help assess these patients' cognitive functions and command following abilities. 20 DOC patients participated in the study and performed 10 vibro-tactile P300 BCI sessions over 10 days with 8-12 runs each day. Vibrotactile tactors were placed on the each patient's left and right wrists and one foot. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Another possible application of bidirectional BCI framework is direct brain-to-brain communication (Grau et al, 2014 ; Rao et al, 2014 ). Moreover, some BCI applications require auxiliary modalities, e.g., proprioceptive feedback and functional electrical stimulation driven by brain signals as feedback for augmenting or regaining peripheral motor actions (Darvishi et al, 2017 ; Bhattacharyya et al, 2019 ; Bockbrader et al, 2019 ; Murovec et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible application of bidirectional BCI framework is direct brain-to-brain communication (Grau et al, 2014 ; Rao et al, 2014 ). Moreover, some BCI applications require auxiliary modalities, e.g., proprioceptive feedback and functional electrical stimulation driven by brain signals as feedback for augmenting or regaining peripheral motor actions (Darvishi et al, 2017 ; Bhattacharyya et al, 2019 ; Bockbrader et al, 2019 ; Murovec et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brain-computer interface (BCI) technology translates cerebral electrical activity, typically recorded by EEG, into computer commands bypassing other body functions [ 6 , 7 ]. Despite having used BCI systems efficiently for rehabilitation purposes [ 8 , 9 ], their introduction in the critical care context is limited [ 10 12 ]. Implementation of BCI systems in critical care settings has faced a number of technical and logistical challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Auditory-based BCI tasks may be most promising, but are not without their own set of challenges. Auditory BCI studies with critically ill patients have often reported high variability and/or poor performance in a single session [ 12 ]. Multiple sessions pose challenges in a hectic ICU setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silvoni et al [ 29 ] investigated the tactile ERP and classification accuracy in a sample of ALS patients and found no significant differences in the accuracy between ALS patients and healthy participants, proving the feasibility of tactile BCI for patients with diseases. Most recently, Murovec et al [ 30 ] demonstrated the potential of communicating by a tactile BCI system for patients with disorders of consciousness.…”
Section: Introductionmentioning
confidence: 99%